Association between social trust and the risk of cardiovascular disease in older adults in Korea: a nationwide retrospective cohort study - Seo Eun Hwang; Seulggie Choi; Kyuwoong Kim; Jong-Koo Lee; Juhwan Oh; Sang Min Park (BMC, 2020)
Abstract Background Although social capital has been shown to be one of the important social determinants of health, the association between social trust and the risk of cardiovascular disease (CVD) is not clear yet. We aimed to investigate the association of social trust with CVD risk using a large Korean population based data. Methods The data of this study was derived from the Korean National Health Insurance Service database. Community-level social trust was determined from the Korean Community Health Survey. The study population consisted of 2,156,829 participants. According to social trust index measured in the area of residence during 2011, participants were followed-up from 1 January 2012 to 31 December 2016. Multivariate Cox proportional hazards regression was used to determine the adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for CVD risk according to quintiles of social trust. Results Compared to participants with the lowest quintile of social trust, those within the highest quintile had lower risk for CVD (aHR 0.91, 95% CI = 0.89 to 0.93), CHD (aHR 0.92, 95% CI = 0.89 to 0.95), and stroke (aHR 0.90, 95% CI = 0.87 to 0.93). The risk-reducing association of high social trust on CVD risk was preserved after additional adjustments for lifestyle behaviors including smoking, alcohol consumption, and physical activity. Conclusion Higher social trust was associated with reduced risk of CVD even after considering lifestyle behaviors. Social trust in a community level is an important determinant of CVD and enhancing social trust may lead to reduced risk of CVD.